Cassia alata as a potential coagulant in water treatment - Aweng Eh Rak; Ahmad Anwar Mohamed Ismail (2012)
Cassia alata or locally known as “pokok gelenggang” is a wild legume species found in Kelantan. Cassia alata based coagulant-flocculant was tested for surface water collected from the Kelantan River. The plant leaves was used to test coagulant rate and dose. The turbidity and other physico-chemicals of surface water sample were measured before and after the jar-test by using portable instruments. Turbidimeter Hanna Model 2100P was used to measure turbidity, while, portable pH meter hand-held Model C535 was used to measure pH. Meanwhile, iron and manganese were measured by using spectrophotometer model DR 2800. Total suspended solids were analyzed using method used by Michaud. The experiments were carried out with coagulant dosage of 0.5, 1.0, 1.5, 2.0, 2.5 and 3 mL/L with the intervals of 0.5 mL/L. The results have shown that Cassia alata leaves can remove turbidity up to 93.33% at the optimal dosage of 1.0 mL/L. In addition, the potential of Cassia alata leaves to remove other pollutants presence in the river water like suspended solids, ferum, manganese and pH was also identified. On the other hand, the leaves of Cassia alata can remove suspended solids by 56.4% but not other parameters.